Association Between Genetic Variation in Blood Pressure and Increased Lifetime Risk of Peripheral Artery Disease. Issue 6 (15th April 2021) - Levin, Michael G.; Klarin, Derek; Walker, Venexia M.; Gill, Dipender; Lynch, Julie; Hellwege, Jacklyn N.; Keaton, Jacob M.; Lee, Kyung M.; Assimes, Themistocles L.; Natarajan, Pradeep; Hung, Adriana M.; Edwards, Todd L.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: We aimed to estimate the effect of blood pressure (BP) traits and BP-lowering medications (via genetic proxies) on peripheral artery disease. Approach and Results: Genome-wide association studies summary statistics were obtained for BP, peripheral artery disease (PAD), and coronary artery disease. Causal effects of BP on PAD were estimated by 2-sample Mendelian randomization using a range of pleiotropy-robust methods. Increased systolic BP (SBP), diastolic BP, mean arterial pressure (MAP), and pulse pressure each significantly increased risk of PAD (SBP odds ratio [OR], 1.20 [1.16–1.25] per 10 mm Hg increase, P =1×10 −24 ; diastolic BP OR, 1.27 [1.18–1.35], P =4×10 −11 ; MAP OR, 1.26 [1.19–1.33], P =6×10 −16 ; pulse pressure OR, 1.31 [1.24–1.39], P =9×10 −23 ). The effects of SBP, diastolic BP, and MAP were greater for coronary artery disease than PAD (SBP ratio of OR [ROR], 1.06 [1.0–1.12], P = 0.04; MAP ratio of OR, 1.15 [1.06–1.26], P =8.6×10 −4 ; diastolic BP ratio of OR, 1.21 [1.08–1.35], P =6.9×10 −4 ). Considered jointly, both pulse pressure and MAP directly increased risk of PAD (pulse pressure OR, 1.26 [1.17–1.35], P =3×10 −10 ; MAP OR, 1.14 [1.06–1.23], P =2×10 −4 ). The effects of antihypertensive medications were estimated using genetic instruments. SBP-lowering via β-blocker (OR, 0.74 per 10 mm Hg decrease in SBP [95% CI, 0.65–0.84]; P =5×10 −6 ), loop diuretic (OR, 0.66 [0.48–0.91], P =0.01), and thiazide diuretic (OR, 0.57 [0.41–0.79], P =6×10 −4 ) associated variants were protective of PAD. Conclusions: Higher BP is likely to cause PAD. BP-lowering through β blockers, loop diuretics, and thiazide diuretics (as proxied by genetic variants) was associated with decreased risk of PAD. Future study is needed to clarify the specific mechanisms by which BP influences PAD.